Ensaios sobre as tecnologias de automação no mercado de trabalho brasileiro - Adamczyk, Willian Boschetti (2021)
What is the future effect of automation technologies on the Brazilian job market? We answer this question with three essays. Firstly, we evaluate the effects of automation technologies on the public sector employment, introducing the Bartik Occupational Task (BOT) method, in order to build estimates on automation susceptibility of each occupation. Secondly, we approximate the deficit of public workers due to retirement, investigating automation as an alternative to replace them. Thirdly, we analyze the future trends for Brazil’s private job market applying the new automation estimates.